Identification in dynamic binary choice models - Gary Chamberlain (SERIEs - Journal of the Spanish Economic Association, 2023)
This paper studies identification in a binary choice panel data model with choice probabilities depending on a lagged outcome, additional observed regressors and an unobserved unit-specific effect. It is shown that with two consecutive periods of data identification is not possible (in a neighborhood of zero), even in the logistic case.
Keywords: C23; C33; 330; Panel data; Binary choice; Feedback; Identification